The development and evaluation of an online educational tool for the evidence-based management of neck pain by chiropractic teaching faculty - Verville, Leslie (J Chiropr Educ, 2020)
OBJECTIVE: To develop an online, interactive educational tool to deliver an evidence-based clinical practice guideline to faculty members at a Canadian chiropractic college. Second, to evaluate the learning, design, and engagement constructs of the tool in a sample of chiropractic faculty members. METHODS: Using an integrated knowledge translation methodology and the Knowledge to Action Framework, we developed an evidence-based online learning tool. The context of the tool focused on a clinical practice guideline on the management of neck pain. We evaluated the learning, design, and engagement constructs in a sample of faculty members and residents using the Learning Object Evaluation Scale for Students. Participants were also asked to provide suggestions for improvement of the tool. RESULTS: Sixteen participants completed the evaluation. Most (68.8%) participants were chiropractors, 75% were male and 56% were between the ages of 25 and 44 years. At least 75% of participants agreed that the learning, design, and engagement constructs of the learning tool were adequate. The open-ended suggestions unveiled 3 pedagogical themes, relating to multimedia, thinking skills, and learner control, within the tool that could benefit from further development. These themes informed recommendations to improve the tool. CONCLUSION: Our online, interactive, module-based learning tool has sound pedagogical properties. Further research is needed to determine if its use is associated with a change in knowledge.